First-Principles Study on the CO2 Reduction Reaction (CO2RR) Performance of h-BN-Based Single-Atom Catalysts Modified with Transition Metals - Xiansheng Yu; Can Zhao; Qiaoyue Chen; Lai Wei; Xucai Zhao; Lili Zhang; Liqian Wu; Yineng Huang (Nanomaterials)
The reasonable design of low-cost, high-activity single-atom catalysts (SACs) is crucial for achieving highly efficient electrochemical CO2RR. In this study, we systematically explore, using density functional theory (DFT), the performance of transition metal (TM = Mn, Fe, Co, Ni, Cu, Zn)-doped defect-type hexagonal boron nitride (h-BN) SACs TM@B−1N (B vacancy) and TM@BN−1 (N vacancy) in both CO2RR and the hydrogen evolution reaction (HER). Integrated crystal orbital Hamiltonian population (ICOHP) analysis reveals that these catalysts weaken the sp orbital hybridization of CO2, which promotes the formation of radical-state intermediates and significantly reduces the energy barrier for the hydrogenation reaction. Therefore, these theoretical calculations indicate that the Mn, Fe, Co@B−1N, and Co@BN−1 systems demonstrate excellent CO2 chemical adsorption properties. In the CO2RR pathway, Mn@B−1N exhibits the lowest limiting potential (UL = −0.524 V), and its higher d-band center (−0.334 eV), which aligns optimally with the adsorbate orbitals, highlights its excellent catalytic activity. Notably, Co@BN−1 exhibits the highest activity in HER, while UL is −0.217 V. Furthermore, comparative analysis reveals that Mn@B−1N shows 16.4 times higher selectivity for CO2RR than for HER. This study provides a theoretical framework for designing bifunctional SACs with selective reaction pathways. Mn@B−1N shows considerable potential for selective CO2 conversion, while Co@BN−1 demonstrates promising prospects for efficient hydrogen production.